Molecular characterisation of the early metastatic phenotype in colorectal cancer - Sculthorpe, Declan (2024)
Colorectal cancer (CRC) is a leading cause of cancer-related mortality, primarily due to its propensity for invasion and metastasis. The progression of CRC involves a series of complex and poorly understood biological events, including tumour invasion into surrounding tissues, lymphovascular infiltration, and the establishment of metastases in regional lymph nodes and distant organs. These processes are critical to understanding CRC's aggressiveness and are of both clinical and biological significance.